COMPARISON OF CONVENTIONAL GAUZE THERAPY WITH VACUUM ASSISTED CLOSURE WOUND THERAPY IN ACUTE TRAUMATIC WOUNDS: Acute Traumatic Wounds - Naqi, Maj Shahid Hussain; ., Meezan Jalil; ., Qasim Butt; Malik, Zaka Ullah (Pakistan Armed Forces Medical Journal, 2013)
Objective: To compare the Vacuum Assisted Closure (VAC) wound therapy with Conventional Gauze Therapy (CGT) in management of acute traumatic wounds on the basis of time taken to achieve a vital red wound ready for definitive surgical closure. Study Design: Randomized control trial. Place and Duration of Study: Department of Surgery Combined Military Hospital Rawalpindi from Mar 2009 to Sep 2009. Patients and Methods: This study included 82 patients of acute traumatic wounds. Patients were randomly allotted to group A, in which wound was treated with new method of vacuum assisted closure (VAC) wound therapy and to group B, in which wound was managed by conventional gauze therapy (CGT). Outcomes were measured by the presence of vital red wound ready to be closed by surgical intervention. Patients with concomitant systemic pathology were not included in study. Results: Comparison between the two groups revealed mean time for wound healing 13 days in group A and 16.9 days in group B with significant difference (p value =0.029). Conclusion: Vacuum assisted closure wound therapy is an effective method in reducing time of wound healing for definitive surgical closure.